2000
DOI: 10.1128/mcb.20.16.5939-5946.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Two Proteins Pat1p (Mrt1p) and Spb8p Interact In Vivo, Are Required for mRNA Decay, and Are Functionally Linked to Pab1p

Abstract: We report here the characterization of a bypass suppressor of pab1⌬ which leads to a fourfold stabilization of the unstable MFA2 mRNA. Cloning of the wild-type gene for that suppressor reveals that it is identical to PAT1 (YCR077c), a gene whose product was reported to interact with Top2p. PAT1 is not an essential gene, but its deletion leads to a thermosensitive phenotype. Further analysis has shown that PAT1 is allelic with mrt1-3, a mutation previously reported to affect decapping and to bypass suppress pab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
138
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(154 citation statements)
references
References 56 publications
15
138
0
Order By: Relevance
“…MRN is required for end resection and homologous recombination (reviewed in Williams et al 2007). We also isolated snf22 (two alleles), a SNF2-related ATPase characterized for its role in chromatin remodeling in meiosis (Yamada et al 2004); swi9/rad16, the ScRAD1 ortholog required for excision repair and some forms of recombination (Carr et al 1994;Farah et al 2005); and a mutation in SPBC19G7.10c, encoding an uncharacterized homolog of the topoisomerase-interacting S. cerevisiae Pat1 protein required for mRNA decapping (Wang et al 1996;Bonnerot et al 2000). We were unable to identify the genes corresponding to two mutations, rad37 and rad39.…”
Section: Resultsmentioning
confidence: 99%
“…MRN is required for end resection and homologous recombination (reviewed in Williams et al 2007). We also isolated snf22 (two alleles), a SNF2-related ATPase characterized for its role in chromatin remodeling in meiosis (Yamada et al 2004); swi9/rad16, the ScRAD1 ortholog required for excision repair and some forms of recombination (Carr et al 1994;Farah et al 2005); and a mutation in SPBC19G7.10c, encoding an uncharacterized homolog of the topoisomerase-interacting S. cerevisiae Pat1 protein required for mRNA decapping (Wang et al 1996;Bonnerot et al 2000). We were unable to identify the genes corresponding to two mutations, rad37 and rad39.…”
Section: Resultsmentioning
confidence: 99%
“…The process and regulation of mRNA turnover is a fundamental aspect of gene expression+ A major pathway of mRNA turnover for both stable and unstable transcripts has been identified in Saccharomyces cerevisiae+ In this pathway, degradation is initiated by deadenylation of the 39 poly(A) tail (Muhlrad & Parker, 1992;Decker & Parker, 1993)+ In yeast, deadenylation is followed by removal of the 59 m7 GpppN cap structure, and exonucleolytic digestion in a 59-39 direction (Decker & Parker, 1993;Hsu & Stevens, 1993;Beelman et al+, 1996)+ Poly(A) shortening requires two proteins, Ccr4p and Pop2p, which have recently been shown to be components of the yeast deadenylase )+ Following deadenylation, the Dcp1p/Dcp2p decapping complex decaps mRNAs at their 59 end Dunckley & Parker 1999)+ Although Dcp1p and Dcp2p are the only proteins known to be required for decapping (Dunckley & Parker, 1999, the rate of decapping is affected by several trans-acting factors+ These accessory factors include Pat1p/Mrt1p, the Lsm complex (consisting of Lsm1p-Lsm7p), Vps16p, Edc1p, and Edc2p Zhang et al+, 1999;Bonnerot et al+, 2000;Tharun et al+, 2000;Wyers et al+, 2000;Dunckley et al+, 2001)+ Pat1p/Mrt1p was originally identified as a genetic lesion that slows mRNA decapping, and was later shown to also be required for efficient translational initiation Wyers et al+, 2000)+ There are nine Lsm proteins in yeast, which form two distinct seven-member ring structures of differing function (Salgado-Garrido et al+, 1999)+ Lsm2p-Lsm8p associate in the nucleus and are involved in U6 snRNA metabolism, whereas Lsm1p-Lsm7p associate in the cytoplasm and affect decapping of mRNAs (Mayes et al+, 1999;Bouveret et al+, 2000;Tharun et al+, 2000)+ Vps16p was identified as a mutant that affected decapping rates in vitro, and Edc1p and Edc2p have been shown to be in a complex with Dcp1p and Dcp2p (Zhang et al+, 1999;Dunckley et al+, 2001)+ Although the mechanism of how these proteins en-hance decapping is unclear, it is possible a class of decapping enhancers may do so by directly affecting the translatability of the mRNA+ Indeed, translational repression may be a first step required for efficient decapping, as recent studies have shown the cap-binding protein, eIF-4E, can inhibit decapping activity both in vivo and in vitro (Schwartz & Parker, 1999+ Given this, a critical issue to resolve in understanding mRNA decay is to determine the nature of transitions between translating and nontranslating states of mRNAs+…”
Section: Introductionmentioning
confidence: 99%
“…It is followed by the removal of the 5Ј-cap structure by the Dcp1p decapping enzyme, which exposes the body of the transcript to Xrn1p,23). A complex of seven Lsm proteins (including Spb8p/Lsm1p) and Pat1p has been shown to interact with mRNA and to be required for mRNA decapping (20,(23)(24)(25)(26).…”
mentioning
confidence: 99%